(untitled) (BioLaw Journal - Rivista di BioDiritto, 2024)
In respect of the multidimensional implications of Artificial Intelligence systems, this writing intends to focus on relational aspects, particularly regarding minors who build their personal identity and develop their personality through social relationships. Recent European acts, such as the Digital Services Act and the Artificial Intelligence Act, offer some safeguards that need to be complemented by the traditional constitutional duties of education entrusted to families and schools. The objective of the paper is to “update” the understanding of the constitutional framework within which such duties are embedded, both for the protection and empowerment of minors in order to incorporate the “virtuality” of artificial intelligence systems.